2007
DOI: 10.2981/0909-6396(2007)13[417:coelll]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Eurasian lynx Lynx lynx den sites and kitten survival

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 20 publications
(30 reference statements)
0
25
0
Order By: Relevance
“…Although other studies have identified rocky sites as important for lynx, e.g. for den site selection (Boutros et al 2007), increased hunting success (Krofel et al 2007) and scent marking (Vogt et al 2014), our study is to the best of our knowledge the first to empirically stress the significance of rock formations as resting habitats for lynx. In general, Table 1.…”
Section: Discussionmentioning
confidence: 72%
“…Although other studies have identified rocky sites as important for lynx, e.g. for den site selection (Boutros et al 2007), increased hunting success (Krofel et al 2007) and scent marking (Vogt et al 2014), our study is to the best of our knowledge the first to empirically stress the significance of rock formations as resting habitats for lynx. In general, Table 1.…”
Section: Discussionmentioning
confidence: 72%
“…Contrary to other carnivore‐denning studies (Boutros et al ., ; May et al ., ), lynx in the northern study site preferentially selected den sites at lower, rather than higher, elevations. Other authors (Petram, Knauer & Kaczensky, ) have suggested dens at higher elevations reduce encounters with humans.…”
Section: Discussionmentioning
confidence: 98%
“…The most consistent feature that lynx selected for across Norway was den sites that were associated with more rugged terrain than available, similar to denning lynx elsewhere in Europe (Boutros et al ., ; Krofel, Skrbinšek & Kos, ). Rugged terrain potentially reduces disturbance and mortality risk by limiting human access (Magoun & Copeland, ; Ross et al ., ) and likely shelters lynx kittens from the elements (Boutros et al ., ). Considering the retrospective nature of this study, microstructural features of each natal den site were not investigated, but rocky outcrops that offer shelter and dense vegetation at the den also likely influence den selection across Norway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1997;Jobin et al 2000;Odden et al 2006). Similar methods were used to study maternal behavior and reproduction (Schaller 1972;Bothma and le Riche 1984;Schmidt 1998;Boutros et al 2007). While these techniques can provide desired results, they are labor-intensive and usually costly.…”
Section: Introductionmentioning
confidence: 99%